The effect of scaling methods on the calculation of environmental indices - Adamczyk, Joanna (Ecological Questions, 2013)
Landscape structure quantification is a subject of great interest in the environmental sciences because of the practical advantages it offers, including calculation of the environmental indices useful for land management, ecology and many other fields. A trend of developing new systems of environmental indices can be observed in European Institutions such as EEA and EUROSTAT, but there has been criticism about approaches based on Corine Land Cover (CLC). One of the aims of this article is to review the method of this database preparation for the purpose of calculating environmental indices. This study tests the ability of three methods to scale categorical maps and retaining as much of the original landscape structure information as possible. The vector scaling method is comparable to the preparation of the CLC data. Two other methods use Geo-Object Image Analysis as the main tool for classification. The scaling is performed in this method through building a hierarchy of objects and scaling the raster imagery. The results are compared and evaluated for scale effects and the calculation of environmental indices on the basis of the scaled data. There is no universal method for all the characteristics of the landscape pattern. The GEOBIA-based methods demonstrate greater applicability to fine grained structural and landscape configuration analyses. The vector scaling method is applicable mainly to landscape configuration, its results are also better for visualization of the scaled map.